2009
DOI: 10.7191/neurol_bull.2009.1004
|View full text |Cite
|
Sign up to set email alerts
|

Use of Actigraphy in Neurological Patient Populations

Abstract: An actigraph is a portable device that measures movement, usually of the non-dominant wrist, to estimate rest-activity patterns and sleepwake cycles. The use of actigraphy has grown over the past decade. Actigraphy has gained favor in the sleep community for the evaluation of insomnia and circadian rhythm disorders, and the device has become an important research tool. As sleep disorders are common in neurological patient populations, the use of actigraphy has increased in the clinical evaluation of neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A more practical and low-cost solution for gait analysis is ambulatory actigraphy which consists of a piezoelectric accelerometer designed to record body movements. Actigraphy has previously been used in the assessment of various disorders including sleep–wake disorders, hyperactivity disorders, and dementia [ 22 24 , 26 28 ]. The present study aims at exploring the relation between gait parameters, measured by means of ambulatory actigraphy during a single and dual task, and cognitive impairment in order to obtain more insights into the utility of such a paradigm as an additional indicator for the diagnosis of MCI and early AD.…”
Section: Introductionmentioning
confidence: 99%
“…A more practical and low-cost solution for gait analysis is ambulatory actigraphy which consists of a piezoelectric accelerometer designed to record body movements. Actigraphy has previously been used in the assessment of various disorders including sleep–wake disorders, hyperactivity disorders, and dementia [ 22 24 , 26 28 ]. The present study aims at exploring the relation between gait parameters, measured by means of ambulatory actigraphy during a single and dual task, and cognitive impairment in order to obtain more insights into the utility of such a paradigm as an additional indicator for the diagnosis of MCI and early AD.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional analysis techniques involve estimates of sleep/wake status based on the activity data to calculate sleep endpoints such as total sleep time and sleep efficiency (Cole et al 1992). This approach has been useful in many clinical trials (Korszun et al 2002, Deak 2009, Agarwal and Light 2010, Fung et al 2012. However, a more objective and mathematical approach to the analysis of the data may be able to overcome the limitations of these conventional endpoints and analysis methods and increase the ability of actigraphy to help define the physical aspects of diseases (Peterson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The current study is an ancillary research to the 'Sweet-HOME project', specifically aimed at evaluating actigraphic measurements collected during IADLs' assessment, motor task performance, and a free scenario phase. Ambulatory actigraphy, consisting of a piezoelectric accelerometer designed to record body locomotor activity, has been previously used to evaluate various disorders including sleep-wake disorders, hyperactivity disorders, and dementia [8][9][10]. Recent studies have shown that daytime motor activity is reduced in AD patients compared to healthy controls [11][12][13].…”
Section: Introductionmentioning
confidence: 99%